Adam Watkins' 8th Birthday Party - Watkins, Howard::::::::: (1986)
Adam Watkins blowing out # 8 candle on birthday cake; Carolyn Roelke, Seth Tilley, Devon Bleile-Kratzer, Art Wille, Adam, Rachel Roelke